2014
DOI: 10.12691/wjar-2-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Path Analysis Studies in Tomato (<i>Solanumlycopersicon</i>l.) Genotpes under Humera, Northern Ethiopia Condition

Abstract: In order to evaluate performance of genotypes and study the direct and indirect effects of characters on fruit yield, thirty six tomato genotypes introduced from different countries were grown at Humera Agricultural Research Center during 2010/11 cropping season under irrigation condition. The trial was laid out in 6 x 6 simple lattice design in two replications. The maximum marketable yield was obtained from the genotype CLN-2037-A (49.20 tons ha-1) and the minimum with H-1350 (3.00 tons ha-1). Estimates of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…Like that of drip irrigation, significantly lower tomato single fruit weight (60 g) was observed under Melkashola while the highest one was recorded under Fetan (88.5 g). This is in agreement with the finding of [19], who reported a wide range of difference (40.4 -86.4 g). Comparing the yield which is the most important parameter, significantly different yield was seen among some varieties.…”
Section: Yield and Other Parameters Of Tomato Varieties Underfurrow Isupporting
confidence: 93%
See 1 more Smart Citation
“…Like that of drip irrigation, significantly lower tomato single fruit weight (60 g) was observed under Melkashola while the highest one was recorded under Fetan (88.5 g). This is in agreement with the finding of [19], who reported a wide range of difference (40.4 -86.4 g). Comparing the yield which is the most important parameter, significantly different yield was seen among some varieties.…”
Section: Yield and Other Parameters Of Tomato Varieties Underfurrow Isupporting
confidence: 93%
“…Relatively higher mean yield of tomato (44.09 ton ha -1 ) was recorded under drip irrigation than furrow one (43.38 ton ha -1 ) ( Table 5). In line with results of this study, [19], [17] reported that yieldof tomato under drip system was found higher by 44% and 47% respectively as compared to the surface irrigation method. So considering the yield, as the most parameters for comparison between the two systems, all tomato varieties were showed better yield under drip than furrow irrigation system (Table 1 and 3).…”
Section: Comparison Of Yield and Yield Related Parameters Of Tomato Usupporting
confidence: 89%
“…Whereas, the number of primary branches plant -1 at flowering, days to first flowering, node at which first flowering cluster appears, days from fruit set to fruit maturity, total soluble solids and total sugars showed a moderate genetic advance. These results were found to be in consonance with the results of Samadia et al (2006) for plant height, Kumar et al (2006) for the number of primary branches plant -1 , Mehta and Asati (2008) and Pemba Sherpa et al (2014) for days to first flowering, Mohanty (2003) for the number of flowers cluster -1 and the number of flower clusters (truss) plant -1 , Chernet (2013) for per cent fruit set, Kumar et al (2013) for the number of fruits cluster -1 and the number of fruits plant -1 , Dufera (2013) for fruit length and fruit girth, Dar and Sharma (2011) for fruit weight, Rathod (2014) for yield plant -1 and the number of locules fruit -1 , Kumar et al (2013) for weight of seeds fruit -1 , Shokat et al (2013) for fruit firmness, Saini et al (2013) for pericarp thickness, Reddy et al (2013) for shelf life of fruits, Nadeem et al (2013) for total soluble solids, Rathod (2014) for titrable acidity, ascorbic acid, lycopene, total carotenoids and total sugars.…”
Section: Slsupporting
confidence: 83%
“…The present finding for pericarp thickness were supported by [22] who investigated various genotypes of tomato at Southwestern Romania. Thirty six tomato genotypes were studied and similar values for pericarp thickness 0.38 to 0.84 were observed [14].These may be due the differences in the genetic makeup, genetic potential of the genotypes and the environment study area.…”
Section: Fruit Weight (Gm)mentioning
confidence: 81%